Heritage, Tourism and Emotion - Fortuna, Carlos (2013)
The present paper starts with a discussion of the relationship between heritage and tradition and proceeds to address the complex process of assigning meaning to heritage and to objects, places and sociocultural practices. In this context, tourism presents itself as a powerful means of enhancing the emotional significance of such objects, places and social practices. The current pursuit of emotional experiences plays a key role not just in the development of memory tourism, but also in dark tourism and reality tourism. The different ways in which those experiences are perceived are seen here as modes of social dispute over meanings. Today’s emphasis on the psycho-emotional aspects of the tourist experience suggests the possibility of a sharp worldwide increase in tourist supply of a strong emotional kind.